Quatum deletion: photonic simulation and relevance as No-Go Theorem - Gatti Alvarez, Giancarlo (2016)
This thesis discusses the No-Deleting Theorem in the context of quantum mechanics, and from an informational and thermodynamic point of view. The theorem is proved, and distinction is made between deletion and erasure. Erasure is further discussed through Maxwell’s Demon and Landauer’s principle, which are linked to one another by the Second Law of Thermodynamics. This leads to relate erasure with measurement and work. A setup for deletion simulation is proposed by use of linear optics supplemented by processes such as spontaneous parametric down-conversion. Finally, the No-Deleting Theorem is compared to other No-Go Theorems, and implication relations are proved (demonstrated) between it, the No-Signalling Theorem and the Second Law of Thermodynamics.Termodinámica. Esto conduce a relacionar el concepto de borrado (erasure) con medición y trabajo. Se propone un montaje experimental que sirve como simulación de un proceso de borrado cuántico (deletion), a través del uso de óptica lineal suplementada por procesos como la conversión paramétrica espontánea descendiente. Finalmente, se compara al Teorema de No-Borrado con otros Teoremas de Imposibilidad, y se demuestran las relaciones de implicancia entre este teorema, el de No-Comunicación y la Segunda Ley de la Termodinámica.